Acral papular mucinosis: a new case of this rare entity - María Encarnación Gómez Sánchez; Fernando de Manueles Marcos; Maria Luisa Martínez Martínez; Roberto Vera Berón; Jose Manuel Azaña Défez (Sociedade Brasileira de Dermatologia, 2016)
Abstract Acral persistent papular mucinosis (APPM) is a rare subtype of localized lichen myxedematosus. It consists of small papules localized exclusively on the back of the hands, wrists and extensor aspects of distal forearms with no other clinical or laboratory manifestations. The lesions tend to persist and may increase slowly in number. Histologically, hematoxylin-eosin and Alcian blue staining demonstrate mucin accumulation in the upper reticular dermis with separation of collagen fibers as a result of hyaluronic acid deposition. Treatment is rarely necessary due to the absence of symptoms. We present a 27-year-old healthy woman with asymptomatic papules on her upper extremities, which adequately meet clinical and pathological criteria of acral papular mucinosis.